Examining the relationships of selected personal antecedent variables and occupational stressors with three burnout dimensions a closer look at job burnout in Philippine call centers - Quesada, Suzette Angeles (2008)
This study examined burnout in 150 Filipino inbound call center agents from three selected companies in Metro Manila area using a survey questionnaire measuring their attitudes toward 13 pre-tested occupational stressors and 22 adapted items from the Maslach burnout inventory (MBI) survey. The realationships among the burnout dimensions (exhaustion, cynicism, and reduced efficacy) and the occupational stressors (physical environment stressors, individual stressors, and organizational stressors) were examined with respect to several antecedent variables (socio-demographic and attitude). For the occupational stressors, the significant antecedent variables were educational attainment, doing further studies, previous work experience, length of stay with the company, plans for a promotion, adn plans of leaving the company. For the burnout dimensions, the significant antecedent variables were gender, civil status, doing further studies, previous work experience, and plans of leaving the company. For exhaustion, correlations were found for the stressors poor audio, personal space, irate callers, room for professional growth, schedule changes, time pressure, pay issues, and consistencies of policies. Its best predictors were personal space, room for professional growth, protocol adherence, and pay issues. For cynicism, correlations were found for personal space, irate callers, protocol adherence, schedule changes, room for professional growth, time pressure, pay issues, relationship with teammates, consistency of policies, and company climate. Its best predictors were personal space, irate callers, relationship with teammates, and office politics. For reduced efficacy, correlations were found for poor audio, pay issues, and relationship with teammates. Its best predictors were pay issues, relationship with teammates, and company climate. For over-all burnout, correlations were found for poor audio, personal space, irate callers, protocol adherence, room for professional growth, time pressure, pay issues, relationship with teammates, company climate, and consistency of policies. Its best predictors were personal space, relationship with teammates, and protocol adherence. The male and female FGD groups helped uncover mergent themes in relation to the quantitative results. They revealed several sources and solutions for alleviating burnout, and were thus classified according to two coping classifications: internal changes and external changes.